Implementasi Seni Tari Dalam Pendidikan Islam - Yazida Ichsan (Prodi Pendidikan Agama Islam IAI Al-Qodiri Jember, 2022)
Abstract: The purpose of this research is to find out the values of dance implementation in Islamic education. The method used in this research is literature research which in conducting this research to obtain or collect compiling information using the help of internet applications to browse books, journals and other scientific works related to research topics. Then the data is summarized and focuses on the main thing only then arranged with the theme and pattern that has been determined. The results of this research are dance in Islamic education is able to instill character values such as faith, discipline, perseverance, beauty, manners, patience, craft, and sensitivity of feelings. Islamic education by studying various arts including dance art can be able to learn the very close relationship between art and religion in showing God's beautiful creation and how great the power of Allah SWT. Keywords: Dance, Islamic Education.